Separation of selenium species in plant tissues by high performance liquid chromatography-ultraviolet treatment-hydride generation atomic fluorescence spectrometry using various mobile phases. Issue 1 (1st January 2021) - Han, Dan; Xiong, Shuanglian; Jia, Wei; Chen, Simeng; Wei, Yanqiu; Shao, Huifang; Huang, Wuxing
Abstract: Anion-exchange chromatography (Hamilton, PRP-X100) with hydride-generation atomic fluorescence spectrometry (HG-AFS) is commonly used for selenium (Se) speciation analysis in environmental and biological samples. However, retentions of Se species are often different with different mobile phases. To address it, this study systematically investigated mobile phases based on ammonium salts to obtain good resolution of Se species. Various mobile phases, including NH4 H2 PO4, NH4 Ac, NH4 NO3 and (NH4 )2 HPO4, were tested. The best result was obtained with a mobile phase containing 60 mmol L −1 (NH4 )2 HPO4 at pH 6.0, where the separation of Se species, including selenite [Se(IV)], selenate [Se(VI)], selenocystine (SeCys) and selenomethionine (SeMet), was achieved within 10 min with reasonable resolution. In addition, the recoveries of SeCys, Se (IV), SeMet and Se (VI) in the Se-enriched samples were 95.72 ± 1.60%, 106.89 ± 2.20%, 93.28 ± 2.82% and 91.38 ± 1.27%, respectively. Finally, the proposed method was validated for the determination of Se species in Nicotiana tabacum tissues.